An Insight into Indonesia's Challenges in Implementing Newborn Screening Programs and Their Future Implications - Gilbert Sterling Octavius; Vamela Adman Daleni; Yulita Delfia Sari Sagala (MDPI AG, 2023)
Due to high entry barriers, countries might find it daunting to implement the NBS program, especially those just trying to start it. This review aims to discuss Indonesia's barriers that hinder newborn screening (NBS) implementation while discussing the future implications. Literature in Pubmed and Google Scholar was scoured with keywords such as "Newborn Screening", "Neonatal Screening", "Indonesia", "Asia Pacific", "Barriers", and "Challenges". We also searched for relevant references in those published articles. Grey literature, such as state regulations, informative webinars on the topics by experts regarding current situations, and press releases by the Indonesian Minister of Health (MoH), was also searched. Newborn screening is no longer considered just a laboratory test but an array of well-harmonized systems that must be orchestrated well. Some of the barriers Indonesia faces in implementing NBS are a lack of prevalence data, ethical issues, infrastructure, cost-benefit analysis, logistical issues, government support, patient issues, a lack of commitments, and a lack of healthcare workers, specialization, and training. Government support with professional advocates and support groups, proper infrastructure, and a single-payer system for NBS programs are necessary to accelerate NBS programs in Indonesia.